Experiments and analytical methods in physical chemistry Prof. Jeremy Brown and Dr. Regis Collins. - Collins, Regis; Brown Jeremy (Arcler Press, 2015)
An analytical techniques is a method that is used to determine the concentration of a chemical compound or chemical element. There are a wide variety of techniques used for analysis, from simple weighing to titrations to very advanced techniques using highly specialized instrumentation. This book is divided into ten chapters. Chapter one reviews on catalytic steam reforming of methanol to produce hydrogen on supported metal catalysts. Second chapter discusses the use of hydrogen-methane blends in internal combustion engines. Third chapter describes about the hybrid filtration combustion process. The physical phenomena involved as well as their mathematical description by the governing equations enforcing mass and energy conservation for both the gas and solid phases are discussed. Fourth chapter reviews on techniques and methods used to investigate the interaction of hydrogen with matter. Fifth chapter introduces the fabrication processes for the electrode for MEA. Fabrication processes for the electrode for MEA was briefly reviewed in a view of optimization of processes parameter and application of new supported catalysts. Sixth chapter gives the details about electrode/electrolyte interphase characterization in solid oxide fuel cells. The electrode/electrolyte interphases are the most relevant because they influence the transfer of ions and electrones from one material to the other and thus directly affect cell performance. Seventh chapter mainly focus on the performance improvement as fuel cell can be considered as immature and complex technology. Immaturity is reflected by the rapid technological progress in performance. Whereas, complexity refers to the fact that fuel cells require an overall system that comprises of numerous components between which there is a high degree of independence. Chapter eight is reviewing the use of electrochemical methods to generate OPC from the direct transformation of elemental phosphorus. The electrochemistry is a powerful synthetic method for preparing a wide range of phosphorous compounds. Ninth chapter indicates that the electrochemical behavior of nickel was carried out in sweat-mimic solutions and using a set-up similar to that of the device. Last chapter describes about the cyclohexane. Cyclohexan have a unique thermomorphic nature and led to the development of cyxlohexane-based liquid-biphasic system, which can be well-combined with organic electrochemistry.